Von Willebrand Factor Release and P-Selectin Expression Is Stimulated by Thrombin and Trypsin but not IL-1 in Cultured Human Endothelial Cells - Collins, Peter W; Macey, Marion G; Cahill, Mary R; Newland, Adrian C (Thrombosis and Haemostasis, 1993)
The stimulated release of von Willebrand factor (vWF) from endothelial cells by secretagogues such as thrombin is associated with the translocation of Weibel-Palade bodies to the cell membrane and the surface expression of P-selectin (also known as GMP 140, PADGEM and CD 62). P-selectin, which is stored in Weibel-Palade bodies, is a neutrophil and monocyte adhesion molecule important in the initiation of inflammation.We have developed a simple assay for the detection of P-selectin on endothelial cells using indirect immunofluorescence and flow cytometry and have confirmed that this is temporally related to vWF release. The assay has been used to demonstrate that IL-1 does not cause Weibel-Palade body degranulation but that trypsin does. This has implications for the use of passaged endothelial cells in the study of vWF release and the assay has numerous possible applications in study of mechanisms of stimulated vWF release.